Penobscot man : the life history of a forest tribe in Maine - Speck, Frank G. (Frank Gouldsmith), 1881-1950 (University of Pennsylvania Press : H. Milford, Oxford University Press, 1940)
The doomed flight of two young indentured servants from their unkind master brings together an unlikely assortment of people in a mid-18th-century Pennsylvania town.